2016
DOI: 10.1016/j.pnpbp.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic neuropeptide signaling in alcohol addiction

Abstract: The hypothalamus is now known to regulate alcohol intake in addition to its established role in food intake, in part through neuromodulatory neurochemicals termed neuropeptides. Certain orexigenic neuropeptides act in the hypothalamus to promote alcohol drinking, although they affect different aspects of the drinking response. These neuropeptides, which include galanin, the endogenous opioid enkephalin, and orexin/hypocretin, appear to stimulate alcohol intake not only through mechanisms that promote food inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 182 publications
2
30
0
Order By: Relevance
“…Utilizing this limited access (2hr) paradigm, we have recently shown that binge-like intake of high fat diet (HFD) induced anxiolytic effects and attenuated alcohol consumption in non-dependent rats (Sirohi et al, 2016). This finding could be explained by the length and exposure history of a calorie-rich food, which has fundamentally different behavioral outcomes (Krishna et al, 2016; Tracy et al, 2015) or changes in the feeding peptides, which control behavioral constructs such as motivation and anxiety that also contribute to excess alcohol intake (Barson and Leibowitz, 2016; Morganstern et al, 2011). Therefore, in the present study, we hypothesized that extended intermittent access to HFD would lead to increased alcohol consumption in non-dependent rodents.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Utilizing this limited access (2hr) paradigm, we have recently shown that binge-like intake of high fat diet (HFD) induced anxiolytic effects and attenuated alcohol consumption in non-dependent rats (Sirohi et al, 2016). This finding could be explained by the length and exposure history of a calorie-rich food, which has fundamentally different behavioral outcomes (Krishna et al, 2016; Tracy et al, 2015) or changes in the feeding peptides, which control behavioral constructs such as motivation and anxiety that also contribute to excess alcohol intake (Barson and Leibowitz, 2016; Morganstern et al, 2011). Therefore, in the present study, we hypothesized that extended intermittent access to HFD would lead to increased alcohol consumption in non-dependent rodents.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Over the years, OX – a neuropeptide synthesized in a subgroup of lateral hypothalamic cells which have projections throughout the brain – has been identified to play a role in a number of homeostatic and regulatory behaviors, including feeding, sleep-wake cycle, as well as emotional and neuroendocrine regulation (Brown et al, 2015a; Li et al, 2016; Mahler et al, 2014). OXRs have also been addressed in many studies of drugs of abuse, including cocaine, opioids, nicotine and alcohol (Barson and Leibowitz, 2016; Boutrel et al, 2013; Mahler et al, 2014; Mahler et al, 2012). There are two subtypes of OX receptors, OX1R and OX2R (Mahler et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…). The paraventricular nucleus in particular has been implicated in the relationship between GAL and fat intake (Barson & Leibowitz ). Alcohol is the only drug of abuse that has a caloric content, and the consumption of alcohol results in an increase in circulating lipids as seen in HFDs (Chang et al .…”
Section: Discussionmentioning
confidence: 99%